Kerajaan berkabinet di Malaysia beberapa pemerhatian umum - Abdul Aziz Bari, (Fakulti Undang - Undang, 2001)

(untitled)
The article seeks to highlight the underlying ideas and trends pertaining to the application of cabinet government principles in Malaysia, both at the federal and state levels. Although the principles and foundations of our cabinet system have their origins in the United Kingdom our local landscape – particularly the political system and culture – have conditioned the practice of cabinet government in Malaysia. It is quite interesting to note that some of these elements are not to be found in the cabinet system’s country of origin itself. As far as the future and prospects of reform are concerned it may be a good idea to see how the cabinet government in certain countries, particularly those outside the common law tradition, devised and implement their model of cabinet government. However before that could be done one must be sure that the existing framework has been allowed to work but failed. Apparently our cabinet system of government has been put in place not just as a matter of choice but also to enable us to retain our traditional system. Prominent in this traditional system is the position and role of the monarchy. As a matter of law, the retention of the traditional institution does not make any difference for the monarch’s power is essentially similar to that of an appointed or elected head of state. Nonetheless, as the monarchy is basically a part of the indigenous culture and politics it has a bearing on the working of cabinet system. Apart from the indigenous elements the cabinet system in Malaysia also operates within a federal structure; another factor not to be found in the United Kingdom. All these factors make the study of cabinet government in Malaysia interesting as the Reid Commission Report has recommended that both the rules and conventions of cabinet government in the United Kingdom are to be applied in this country